Addressing Digital Inequality for the Socioeconomically Disadvantaged Through Government Initiatives: Forms of Capital That Affect ICT Utilization - Hsieh, J. J. Po-An; Rai, Arun; Keil, Mark (Information Systems Research, 2011)
Digital inequality, or unequal access to and use of information and communication technologies (ICT), is a severe problem preventing the socioeconomically disadvantaged (SED) from participating in a digital society. To understand the critical resources that contribute to digital inequality and inform public policy for stimulating initial and continued ICT usage by the SED, we drew on capital theories and conducted a field study to investigate: (1) the forms of capital for using ICT and how they differ across potential adopters who are SED and socioeconomically advantaged (SEA); (2) how these forms of capitals are relatively impacted for the SEA and the SED through public policy for ICT access; and (3) how each form of capital influences the SED's intentions to use initially and to continue to use ICT. The context for our study involved a city in the southeastern United States that offered its citizens free ICT access for Internet connectivity. Our results show that SED potential adopters exhibited lower cultural capital but higher social capital relative to the SEA. Moreover, the SED who participated in the city's initiative realized greater positive gains in cultural capital, social capital, and habitus than the SEA. In addition, we find that the SED's initial intention to use ICT was influenced by intrinsic motivation for habitus, self-efficacy for cultural capital, and important referents' expectations and support from acquaintances for social capital. Cultural capital and social cultural capital also complemented each other in driving the SED's initial use intention. The SED's continued use intention was affected by both intrinsic and extrinsic motivations for habitus and both knowledge and self-efficacy for cultural capital but was not affected by social capital. We also make several recommendations for future research on digital inequality and ICT acceptance to extend and apply the proposed capital framework.